If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x = 3(x + -1) + -4(1 + -1x) Reorder the terms: 15x = 3(-1 + x) + -4(1 + -1x) 15x = (-1 * 3 + x * 3) + -4(1 + -1x) 15x = (-3 + 3x) + -4(1 + -1x) 15x = -3 + 3x + (1 * -4 + -1x * -4) 15x = -3 + 3x + (-4 + 4x) Reorder the terms: 15x = -3 + -4 + 3x + 4x Combine like terms: -3 + -4 = -7 15x = -7 + 3x + 4x Combine like terms: 3x + 4x = 7x 15x = -7 + 7x Solving 15x = -7 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 15x + -7x = -7 + 7x + -7x Combine like terms: 15x + -7x = 8x 8x = -7 + 7x + -7x Combine like terms: 7x + -7x = 0 8x = -7 + 0 8x = -7 Divide each side by '8'. x = -0.875 Simplifying x = -0.875
| -3=3(x+6) | | 149-5x=22x+23 | | 5x+13=-137-10x | | 7-5(x-2)=5-3(x+3) | | 11-9x=29-16x | | -9+2z=9z+12 | | 2(x-1)-3(2-x)+4(1-x)=0 | | -23-4x=9-8x | | -134-7x=8x+16 | | -5(k+5)+5k= | | 5(b-4)+25= | | 0=3(2-3x)-7(x-3) | | 10+2(4y+3)= | | 3x-2(12-x)=4(2x-3)+3(x+1) | | 6-5c=-14 | | 6(1-x)+4=3(2-x)-4 | | 4x+10=90-6 | | 40-2(x+1)=90 | | 4k+6=6k-2 | | 6(2x+1)+7=9x+1 | | 6x+9=-119-10x | | 3(7x-1)+8(3-2x)=1 | | -2*5= | | 5(2x+3)-3(x+1)=5 | | 8(x-2)-2(2x-1)=2x+1 | | -2(5r+3)= | | 5a+30b=25 | | 5(3x-4)=8x+1 | | 6a-4=8 | | 3(10a)= | | 2x-3(2-x)=4 | | 4(x+3)-2=2 |